Intranasal Application of Budesonide Attenuates Lipopolysaccharide-Induced Acute Lung Injury by Suppressing Nucleotide-Binding Oligomerization Domain-Like Receptor Family, Pyrin Domain-Containing 3 Inflammasome Activation in Mice - Liang Dong; Yu-Hang Zhu; De-Xing Liu; Juan Li; Peng-Cheng Zhao; Yuan-Ping Zhong; Yong-Qin Chen; Wei Xu; Zhao-Qiong Zhu (Journal of Immunology Research)
Aim. To investigate the protective effects of budesonide against lipopolysaccharide- (LPS-) induced acute lung injury (ALI) in a murine model and its underlying mechanism. Methods. Adult male C57BL/6 mice were divided into three groups: control, ALI, and ALI + budesonide groups. LPS (5 mg/kg) was intratracheally injected to induce ALI in mice. Budesonide (0.5 mg/kg) was intranasally given 1 h before LPS administration in the ALI + budesonide group. Twelve hours after LPS administration, all mice were sacrificed. Hematoxylin-eosin staining and pathological scores were used to evaluate pathological injury. Bronchoalveolar lavage was performed. The numbers of total cells, neutrophils, and macrophages in the bronchoalveolar lavage fluid (BALF) were counted. Enzyme-linked immunosorbent assay was employed to detect the proinflammatory cytokines in BALF and serum, including tumor necrosis factor- (TNF-) α, monocyte chemoattractant protein- (MCP-) 1, and interleukin- (IL-) 1β. The expression of the nucleotide-binding oligomerization domain-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome was detected by western blotting. A lethal dose of LPS (40 mg/kg, intraperitoneally) was injected to evaluate the effects of budesonide on survival rates. Results. Budesonide pretreatment dramatically attenuated pathological injury and reduced pathological scores in mice with ALI. Budesonide pretreatment obviously reduced the numbers of total cells, neutrophils, and macrophages in the BALF of mice with ALI. Additionally, budesonide dramatically reduced TNF-α and MCP-1 expression in the BALF and serum of mice with ALI. Budesonide significantly suppressed NLRP3 and pro-caspase-1 expression in the lung and reduced IL-1β content in the BALF, indicating that budesonide inhibited the activation of the NLRP3 inflammasome. Furthermore, we found that budesonide improved the survival rates of mice with ALI receiving a lethal dose of LPS. Conclusion. Suppression of NLRP3 inflammasome activation in mice via budesonide attenuated lung injury induced by LPS in mice with ALI.